Evaluation of IL-6, CRP and hs-CRP as Early Markers of Neonatal Sepsis - Purushothaman Ganesan; Priyadarshini Shanmugam; Shameem Banu Abdul Sattar; Shenbaga Lalitha Shankar (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Bacterial sepsis is a life threatening crisis with high mortality and morbidity in neonates. Due to non-specific clinical presentation, diagnosis of sepsis is still a challenge. It can be diagnosed by blood culture but it is time consuming. So, a reliable marker is needed for the diagnosis of neonatal sepsis so that early treatment can be initiated. Various cytokines, chemokines, acute phase reactants, cell surface markers and interferons have been evaluated to find out the effective marker for early diagnosis of neonatal sepsis. In this study, levels of IL-6, CRP and hs-CRP have been analysed which would favour the diagnosis of neonatal sepsis. Aim: This study aimed to detect the levels of IL-6, CRP and hs-CRP in clinically suspected cases of neonatal sepsis and to evaluate and analyze the above parameters as the early markers of neonatal sepsis in comparison with blood culture. Materials and Methods: Eighty neonates were included in this study of which 40 were clinically suspected cases of neonatal sepsis who met the inclusion criteria and the other 40 were normal healthy neonates that were taken as controls. After obtaining written informed consent from either parent of all neonates, venous blood samples were collected. Blood culture was performed by conventional method. Estimation of serum IL-6 was done by ELISA method and serum CRP and hs-CRP were done by immunofluorescence assay. Results: The CRP level >13.49 mg/l showed sensitivity and specificity of 80% and 65.70% respectively. The IL-6 >51.29 pg/ml showed sensitivity of 100% and specificity of 62.86% and hs-CRP showed sensitivity of 90% and specificity of 32.86%. Combination of IL-6 and CRP showed sensitivity and specificity of 100% and 75.71% respectively. Conclusion: Our study suggests that IL-6 is a highly sensitive marker and CRP is a more specific marker for the diagnosis of neonatal sepsis. hs-CRP is a less reliable marker. So, the combination of IL-6 and CRP are the better predictors of neonatal sepsis.